Improving Chemistry Learning Outcomes in Electrochemistry through STAD-Cooperative Learning Model in Class X SMK 2 Palembang - Daniel Simanjuntak; Muhammad Hadeli; Meidia Farlina (Pedagogy Review, 2022)
Abstract: The Increase Of Study Chemistry Through Implementation of Cooperative Learning Model Type STAD in Class X TITL 4 SMKN 2 Palembang. Classroom Action Research (PTK) aims to know the improvements studied chemistry students using a learning model of Student Teams Achievement division (STAD). The research was conducted in the class X SMK Negeri 2 Palembang and the object at students of class X TITL 4, amounting to 34 students. The research which is implemented in two cycles. The data obtained from each cycle later in the analysis to know of any amprovement in the learning process and as a corrections to proceed to the next cycle. Data obtained using sheets of observation and instrument test student learning outcomes. Improved student learning outcomes can be seen from using class average and percent students classical. In the first cycle the average score of students is 66.72 with the percentage of students classical is 41.18%. in the second cycle, there is an increase score in student learning by 78.74 with the percentage classical student to 84.84% Keywords: classroom action research,  learning  model  of  stad,  student  learning outcomes.